Annual Plan 1989-90 Andhra Pradesh - Planning Commission (Planning Commission, 1989)
During the first three years in Seventh Plan period widespread adverse seasonal conditions prevailed in the State on account of which agricultural production had a set back. The year 1988-89 has proved to be a good year with good and. evenly distributed rainfall. The targets set under agricultural production are likely to exceed.
Planning Commission (State Plans Division)
Planning Commission (State Plans Division)